Laporan Studi Kelayakan Bisnis LIMA Sarana Bersih - Sabita, Azmi; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
LIMA Sarana Bersih is a business specializing in the production of cleaning equipment, originally founded to support the local community in winning the ADIPURA award. By leveraging local resources and labor from the surrounding area, this business not only heightens community awareness about the importance of cleanliness but also contributes to the local economy by creating jobs. The evaluation of this business covers various aspects, including legal, environmental, market and marketing, technical and technological, management and human resources, finance, and environmental impact assessment (AMDAL). Legally, the business has fulfilled the licensing requirements, ensuring legitimate and secure operations. Environmentally, it employs effective waste management and recycling principles, although it still faces noise pollution issues. Market and marketing analysis show positive community response and significant market potential through cooperation with the Environmental Agency. Technically, the simple technology utilized is efficient for production. In terms of management and human resources, the business successfully empowers local workers through organized management. Financial analysis indicates the business's feasibility with positive NPV, high IRR, and a quick payback period. Lastly, from an AMDAL perspective, the business positively impacts environmental conservation and the local community's economy.